Simplify.
x8 ÷ x4 · x2

Question

Asked 7/18/2013 7:26:57 AM

Updated 5/10/2015 5:26:24 AM

1 Answer/Comment

Flagged by janezeshun [5/10/2015 5:01:24 AM], Edited by jeifunk [5/10/2015 5:26:24 AM]

Question

Asked 7/18/2013 7:26:57 AM

Updated 5/10/2015 5:26:24 AM

1 Answer/Comment

Flagged by janezeshun [5/10/2015 5:01:24 AM], Edited by jeifunk [5/10/2015 5:26:24 AM]

Rating

3

x^8 ÷ x^4 · x^2

= x^4*x^2

= x^6

= x^4*x^2

= x^6

Added 5/10/2015 5:01:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/10/2015 5:26:16 AM]

(4ab - 8a^2 + 12ac) ÷ 4a

Question

Expert Answered

Updated 9/30/2016 3:07:36 PM

1 Answer/Comment

(4ab - 8a^2 + 12ac) ÷ 4a

= (4ab/4a) + (-8a^2/4a) + (12ac/4a)

= -2a + b + 3c

= (4ab/4a) + (-8a^2/4a) + (12ac/4a)

= -2a + b + 3c

Added 9/30/2016 3:07:19 PM

This answer has been confirmed as correct and helpful.

(3x^2 + 2x - 3)(x - 1)
3x2+ 3x- 4
3x3- 5x2- 5x+ 3
3x3-x2- 5x+ 3
3x3+ 5x2- 5x+ 3 **Weegy:** (3x^2 + 2x - 3)(x - 1)= 3x^3 - x^2 - 5x + 3 (More)

Question

Expert Answered

Updated 3/8/2014 1:12:38 PM

0 Answers/Comments

3(2y - 8) - 2y(5 - y)
-2y2+ 16y - 24
-5y - 8
2y2- 4y - 24
2y2+ 16y - 24

Question

Not Answered

Updated 123 days ago|5/25/2018 10:45:08 AM

2 Answers/Comments

[Deleted]

Added 123 days ago|5/25/2018 10:44:41 AM

This answer has been added to the Weegy Knowledgebase

Deleted by jeifunk [5/25/2018 10:44:47 AM]

3(2y - 8) - 2y(5 - y)

= (3)(2y) + (3)(-8) + 2y^2 + (-10y)

=6y+ (-24) + 2y^2 + (-10y)

=(2y^2) + (6y + (-10y)) + (-24)

=2y^2 - 4y - 24

= (3)(2y) + (3)(-8) + 2y^2 + (-10y)

=6y+ (-24) + 2y^2 + (-10y)

=(2y^2) + (6y + (-10y)) + (-24)

=2y^2 - 4y - 24

Added 123 days ago|5/25/2018 10:45:08 AM

This answer has been confirmed as correct and helpful.

Making predictions based on hints or clues within the story, such as Odysseus talking about the wine Maron gave him, is known as ______ .
symbolism
motifs
theme
foreshadowing
plot

Question

Not Answered

Updated 11/25/2015 5:09:24 PM

1 Answer/Comment

Write the quadratic equation in factored form. Be sure to write the entire equation.
x2 - 5x - 24 = 0

Question

Not Answered

Updated 7/5/2014 3:55:28 PM

1 Answer/Comment

x^2 - 5x - 24 = 0 in factored form is (x + 3)(x - 8) = 0.

(x + 3)(x - 8) = 0;

(x + 3) = 0 or (x - 8) = 0;

the roots are: x = -3 or x = 8

(x + 3)(x - 8) = 0;

(x + 3) = 0 or (x - 8) = 0;

the roots are: x = -3 or x = 8

Added 7/5/2014 3:55:28 PM

This answer has been confirmed as correct and helpful.

27,380,711

questions answered

There are no comments.